2014
DOI: 10.1371/journal.pone.0087781
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Infection Modulates the Pharmacokinetics of Oral Enrofloxacin by Targeting P-Glycoprotein in Small Intestine and CYP450 3A in Liver and Kidney of Broilers

Abstract: P-glycoprotein (P-gp) expression determines the absorption, distribution, metabolism and excretion of many drugs in the body. Also, up-regulation of P-gp acts as a defense mechanism against acute inflammation. This study examined expression levels of abcb1 mRNA and localization of P-gp protein in the liver, kidney, duodenum, jejunum and ileum in healthy and E. coli infected broilers by real time RT-PCR and immunohistochemistry. Meanwhile, pharmacokinetics of orally administered enrofloxacin was also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
2
22
1
3
Order By: Relevance
“…porter proteins encoded by ABCB1 and ABCG2 (Pulido et al, 2006;Guo et al, 2013). This drug influences the expression of ABCB1 at protein level after treatment of broilers (Guo et al, 2014) but did not modulate the activity of P-gp, MRP2 and BCRP in chicken splenocytes (Haritova et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…porter proteins encoded by ABCB1 and ABCG2 (Pulido et al, 2006;Guo et al, 2013). This drug influences the expression of ABCB1 at protein level after treatment of broilers (Guo et al, 2014) but did not modulate the activity of P-gp, MRP2 and BCRP in chicken splenocytes (Haritova et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…These changes in ABCB1, ABCC2 and ABCG2 mRNA did not cause alterations in serum levels and pharmacokinetic parameters of orally administered danofloxacin mesylate (Haritova et al, 2008b). Pathological conditions such as E. coli infection and subsequent treatment with enrofloxacin affected P-gp expression at the transcriptional and translation levels (Guo et al, 2014). ABCB1 mRNA and ABCC2 mRNA levels were down-regulated in the gastrointestinal tract of E. coli challenged broilers (Haritova et al, 2008a).…”
Section: Introductionmentioning
confidence: 86%
“…Emerging evidences have shown that the modification of gut microbiota can drastically alter drug clinical effectiveness (Hitchings and Kelly, 2019). Recently, E. coli infection was observed to significantly reduce the absorption of orally administered enrofloxacin in broilers (Guo et al, 2014). Yan Wang reported that berberine treatment lowered blood lipids and glucose effectively only in the high-fat diet (HFD)-fed hamsters with increased levels of nitrate reductase (NR) activity in the gut microbiota (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pilot pharmacokinetic studies with five chicken in a group were designed and conducted according to previous studies 19 , 41 . Further to promising results of the pilot study fifteen adult healthy chickens (42-days-old) averagely weighted 2 ± 0.13 kg were randomly separated into 3 groups for the full study.…”
Section: Methodsmentioning
confidence: 99%
“…Enrofloxacin is a frequently used fluoroquinolone in the poultry industry in China for the medication of infections caused by bacteria, rickettsiae, and mycoplasmas 18 . It has been proved that enrofloxacin is the substrate of P-gp in chicken and pigs 19 , 20 . Therefore, an important line of P-gp investigations is its pharmacokinetic interactions with feed or feed additives and their possible impact on the clinical efficacy of antibiotics.…”
Section: Introductionmentioning
confidence: 99%